Does predation danger on southward migration curtail parental investment by female western sandpipers? - Jamieson Sarah Emily (De Gruyter, 2015)
Theory predicts that if extending parental care delays migratory departure, and if later migration is more dangerous, then parental care should be curtailed to make an earlier departure. Adult western sandpipers (Calidris mauri) depart Alaska in July, and the presence of peregrine falcons (Falco peregrinus) along their route rises steeply during the migratory period. Pacific dunlins (C. alpina pacifica) are ecologically similar, but do not depart Alaska until October, after peregrine passage has peaked. Because peregrine migration begins earlier in years with early snowmelt, we predicted that the curtailment of parental investment by western sandpiper, but not of Pacific dunlins, should be more pronounced in these more dangerous years. We measured breeding phenology of these species on the Yukon Delta National Wildlife Refuge during three seasons with strongly differing snowmelt timing. We found that they initiated breeding simultaneously, and that western sandpipers, but not Pacific dunlins, ceased laying increasingly earlier, provided increasingly less parental care and departed increasingly sooner as snowmelt was earlier. Advancing departure date by the overall average of 5.2d relative to dunlin reduces migratory exposure to peregrines by an estimated 18%. Our results support the hypothesis that natural selection has favored curtailment of parental investment by western sandpipers to advance migratory departure.